Assessing ecosystem resilience to a tropical cyclone based on ecosystem service supply proficiency using geospatial techniques and social responses in coastal Bangladesh. (October 2020) - Islam, Md Ashraful; Paull, David J.; Griffin, Amy L.; Murshed, Sanzida
Abstract: Ecosystem services are essential for the livelihoods of marginalized communities; however, their supply can be severely disturbed when natural hazards impact on low-lying coastal regions. To understand potential disaster impacts on sustainable livelihoods, ecosystem resilience needs to be assessed before and after a disaster. We examined ecosystem resilience to a tropical cyclone in a southwestern coastal region of Bangladesh in terms of its impacts on the ecosystem's service supply proficiency (ESSP). We adopted a two-tiered methodology commencing with landcover mapping using object-based image analysis (OBIA) to identify five distinct landcovers (cropland, mangrove forest, riparian forest, tidal flat, and sandy beach). Then, Likert scores were used to reflect human perceptions of the supply proficiency of three types of ecosystem services (provisioning, regulating, and cultural services) associated with each landcover. The resilience of each landcover type was assessed by integrating maps of damage and recovery with the Likert scores to calculate ESSP scores. A substantial post-cyclone reduction in ESSP scores was revealed. Significant recovery (both short- and long-term) was observed in most of the affected ecosystems, albeit at somewhat different rates for different ecosystems. This study provides a multi-faceted evaluation of cyclone impacts on existing ecosystems and insight into ecosystem behaviour at different temporal phases of a disaster event. Accordingly, the study offers a novel way to study ecosystem resilience to support effective coastal planning within a vulnerable coastal community. Graphical abstract: Image 1 Highlights: We assessed ecosystem resilience after tropical Cyclone Sidr in Bangladesh. Ecosystem service proficiency was monitored during several disaster phases. We used geoinformatics and social responses to map ecosystem service proficiency. Despite severe destruction, most ecosystems recovered significantly. This study provides meaningful insights into post-disaster ecosystem behavior.